Generalised Local Fractional Hermite-Hadamard Type Inequalities on Fractal Sets - Olanipekun, Peter Olamide (Pan-American journal of mathematics, 2024)
Fractal geometry and analysis constitute a growing field, with numerous applications, based on the principles of fractional calculus. Fractals sets are highly effective in improving convex inequalities and their generalisations. In this paper, we establish a generalised notion of convexity. By defining generalised φh-s convex functions, we extend the well known concepts of generalised convex functions, P-functions, Breckner s-convex functions, h-convex functions amongst others. With this definition, we prove Hermite-Hadamard type inequalities for generalised φh-s convex mappings onto fractal sets. Our results are then applied to probability theory.